Association Between ACE I/D Gene Polymorphism and Hypertension in Smokers - Zafar Kayani, Hateem; Riaz, Sana; Hussain, Nageen (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
The main aim is to study the association of ACE I/D polymorphism with healthy smokers. A total of 49 smokers and 49 healthy controls were enrolled in this study. Intron 16 of the ACE gene was amplified by using nested PCR. The possible banding patterns were as follows; DD, 210 bp fragments; II, 264bp and 498 bp fragments; ID, 210 bp, 264 bp, and 498 bp fragments. The subjects comprised of males only. Among 49 subjects the frequency of ACE DD genotype was 75.5% (37/49), II 24.5% (12/49), while no ID genotype was found in the study. All controls showed DD genotype. The association of ACE I/D polymorphism with different levels of blood pressure were found to be significant.